Countdown to 2015: changes in official development assistance to reproductive, maternal, newborn, and child health, and assessment of progress between 2003 and 2012 - Leonardo Arregoces, MSc; Felicity Daly, DrPH; Catherine Pitt, MSc; Justine Hsu, MSc; Melisa Martinez-Alvarez, PhD; Giulia Greco, PhD; Prof. Anne Mills, PhD; Prof. Peter Berman, PhD; Dr. Josephine Borghi, PhD (Elsevier, 2015)
Background: Tracking of aid resources to reproductive, maternal, newborn, and child health (RMNCH) provides timely and crucial information to hold donors accountable. For the first time, we examine flows in official development assistance (ODA) and grants from the Bill & Melinda Gates Foundation (collectively termed ODA+) in relation to the continuum of care for RMNCH and assess progress since 2003. Methods: We coded and analysed financial disbursements for maternal, newborn, and child health (MNCH) and for reproductive health (R*) to all recipient countries worldwide from all donors reporting to the creditor reporting system database for the years 2011-12. We also included grants from the Bill & Melinda Gates Foundation. We analysed trends for MNCH for the period 2003-12 and for R* for the period 2009-12. Findings: ODA+ to RMNCH from all donors to all countries worldwide amounted to US$12·2 billion in 2011 (an 11·8% increase relative to 2010) and $12·8 billion in 2012 (a 5·0% increase relative to 2011). ODA+ to MNCH represents more than 60% of all aid to RMNCH. ODA+ to projects that have newborns as part of the target population has increased 34-fold since 2003. ODA to RMNCH from the 31 donors, which have reported consistently since 2003, to the 75 Countdown priority countries, saw a 3·2% increase in 2011 relative to 2010 ($8·3 billion in 2011), and an 11·8% increase in 2012 relative to 2011 ($9·3 billion in 2012). ODA to RMNCH projects has increased with time, whereas general budget support has continuously declined. Bilateral agencies are still the predominant source of ODA to RMNCH. Increased funding to family planning, nutrition, and immunisation projects were noted in 2011 and 2012. ODA+ has been targeted to RMNCH during the period 2005-12, although there is no evidence of improvements in targeting over time. Interpretation: Despite a reduction in ODA+ in 2011, ODA+ to RMNCH increased in both 2011 and 2012. The increase in funding is encouraging, but continued increases are needed to accelerate progress towards achieving MDGs 4 and 5 and beyond. Funding: Bill & Melinda Gates Foundation.